microWELT: a dynamic microsimulation model for the study of welfare transfer flows in ageing societies from a comparative welfare state perspective - Spielauer, Martin,Horvath, Thomas,Fink, Marian (Österreichisches Institut für Wirtschaftsforschung, 2020)
This paper introduces the microWELT model. Starting from its objectives, we discuss design choices, the model architecture and key features. microWELT provides a demographic projection tool reproducing Eurostat population projections but adding details such as education, intergenerational transmission of education, fertility by education, partnership patterns, and mortality differentials by education. The model integrates transfer flows as captured by the National Transfer Account (NTA) and National Time Transfer Account (NTTA) accounting framework and calculates a set of indicators based on NTA literature. Individual accounts allow the study of transfers over the whole life cycle by cohorts and between generations.
10419/225206
Keywords: Graue Literatur; Microsimulation; Welfare State; Demographic Change; National Transfer Accounts